3(-2x)-(-3x)+1=-2x+22

Simple and best practice solution for 3(-2x)-(-3x)+1=-2x+22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2x)-(-3x)+1=-2x+22 equation:


Simplifying
3(-2x) + -1(-3x) + 1 = -2x + 22

Remove parenthesis around (-2x)
3 * -2x + -1(-3x) + 1 = -2x + 22

Multiply 3 * -2
-6x + -1(-3x) + 1 = -2x + 22

Remove parenthesis around (-3x)
-6x + -1 * -3x + 1 = -2x + 22

Multiply -1 * -3
-6x + 3x + 1 = -2x + 22

Reorder the terms:
1 + -6x + 3x = -2x + 22

Combine like terms: -6x + 3x = -3x
1 + -3x = -2x + 22

Reorder the terms:
1 + -3x = 22 + -2x

Solving
1 + -3x = 22 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
1 + -3x + 2x = 22 + -2x + 2x

Combine like terms: -3x + 2x = -1x
1 + -1x = 22 + -2x + 2x

Combine like terms: -2x + 2x = 0
1 + -1x = 22 + 0
1 + -1x = 22

Add '-1' to each side of the equation.
1 + -1 + -1x = 22 + -1

Combine like terms: 1 + -1 = 0
0 + -1x = 22 + -1
-1x = 22 + -1

Combine like terms: 22 + -1 = 21
-1x = 21

Divide each side by '-1'.
x = -21

Simplifying
x = -21

See similar equations:

| 3x^2+4x+2=x^2+6x | | 75m+.1m=400 | | 8(2w-6)+4(-15w)=0 | | 6.3p=52.92 | | x^2-5x+4=0 | | 8(1-4b)=-35 | | -7t+-4=80 | | 2.5x=16.75 | | 4r-2=3r+6 | | 2(3x+4)-2x=x+17 | | 3f=999 | | 3-4[2-(5y-8)]= | | 4x-3x-6=21 | | -7-3x=8+2 | | 4x+x-3x+7=2x+x | | 8(x+.5)=2x+4 | | -5(2x-9)=2(x-8) | | 4x^2-10=-6x | | 2c+4-3c=-9+c+15 | | 7C+1=50 | | x-4.5=3 | | 10.6p+15=205.8 | | 10=50x | | 8s-12=52 | | -x-3x+20=x | | 3xyz-y+4x-y= | | 45p=168 | | 2f-81=11 | | 27=x+14 | | -36-9x=-12x+3 | | (5x-2)(7x+8)= | | 2(1/2x+1)=-3(2x-1)+4(2x+1) |

Equations solver categories